Hypervalent iodine(iii) induced oxidative olefination of benzylamines using Wittig reagents - Ramavath, Vijayalakshmi; Rupanawar, Bapurao D.; More, Satish G.; Bansode, Ajay H.; Suryavanshi, Gurunath (New Journal of Chemistry, 2021)
We have developed hypervalent iodine(iii) induced oxidative olefination of primary and secondary benzylamines using 2C-Wittig reagents, which provides easy access to alpha,beta-unsaturated esters. Mild reaction conditions, good to excellent yields with high (E) selectivity, and a broad substrate scope are the key features of this reaction. We have successfully carried out the gram-scale synthesis of alpha,beta-unsaturated esters.